Community Engagement in Urban Experiments: Joint Effort for Sustainable Urban Transformation - Treija, Sandra; Stauskis, Gintaras; Korolova, Alisa; Bratuškins, Uģis (Landscape Architecture and Art, 2023)
The increasing complexity of urban regeneration issues has recently made multi-stakeholder collaboration an important part to solve policy problems. While residents form an important part in a variety of collaborative governance processes, approaches used are often criticized as too formal, and lacking more inclusive participation. Therefore, new informal mechanisms of collaboration are sought, to ensure a more effective engagement and representation of population groups. Although community-led participation is the approach that leads to a more effective collaborative process, issues of power and inequality are a challenge in many places in planning practice [13]. Ways of civic empowerment, communication, and negotiation provide participants with transformative learning opportunities so that not only their arguments change but also the participants of the participation process themselves [6]. In order to test urban development ideas, the notion of "urban experiment" has been developed in recent years as a recognized and effective approach. The urban environment is viewed as a creative laboratory for testing the implementation of diverse initiatives and innovations [8]. The inner-city neighbourhoods in many cities are struggling to ensure vitality and liveability, thus these areas often represent a widespread location of urban experiments. In addition to these questions, the problem of community representation manifests itself in many inner cities. The potential to transform city centre streets and vacant areas into user-friendly urban spaces and the impact of those transformations on the city’s livability were recently tested by Riga municipality. Urban experiments varied in scale and form, resulting in street pedestrianization, urban gardens, and other temporary initiatives, which allowed more space for walking and cycling, street sales, social events and other activities. Thus, the aim of this article is to explore processes of testbed planning with regard to the role of community participation in the designing, implementing, and analysing phases of the experiment. After presenting the findings, the article concludes with a discussion on factors that influence public participation in collaborative governance including communication, the balance of interests, and the degree of resident involvement in decision-making.